Edible Flowers, Old Tradition or New Gastronomic Trend: A First Look at Consumption in Portugal versus Costa Rica - Guiné, Raquel (2020)
This study investigated the knowledge and use of edible flowers (EF) in two countries, Portugal, in Europe, and Costa Rica, in Latin America, and aimed to evaluate the similarities and/or differences regarding the utilization of EF in gastronomy. This work consisted of a questionnaire survey, undertaken on a sample of 290 participants. The results indicate that most people surveyed (87%) have heard about EF but believe there is not enough information about them (96%). Only one third of participants consider there are risks associated with the consumption of EF, being those related to toxicity and pesticides. Significant differences (p < 0.05) were found between participants from the two countries but not with different professional areas. About half (48%) of the participants had already consumed EF, mostly for decoration or confection of dishes (77% positive answers) and in salads (75%). The flowers consumed most frequently were chamomile and rose, respectively, in Costa Rica and Portugal. Reasons pointed out to consume EF include decoration, taste, novelty and aroma, while aspects such as nutritional value or antioxidant capacity are prized by fewer consumers. EF were mostly acquired in supermarkets, cultivated at home or collected in the wild. In general, most participants (85%) consider the use of EF in gastronomy interesting, but less than one third (27%) believe we should eat EF more often. Finally, discriminant function analysis revealed that country was the variable for which the differences in the consumption of EF was more pronounced, while education level and age group showed the lowest variability between groups